Respuesta :
Answer:
x=-2
Step-by-step explanation:
first distribute the 2 through x-4 you get 2x-8=6x then subtract 2x from both sides of the equation now you have 4x=-8 then divide 4 from both sides of the equation and you x=-2
Answer:
x = -2
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
2(x−4)=6x
(2)(x)+(2)(−4)=6x (Distribute)
2x + −8 = 6x
2x − 8 = 6x
Step 2: Subtract 6x from both sides.
2x −8 − 6x = 6x − 6x
−4x − 8 = 0
Step 3: Add 8 to both sides.
−4x − 8 + 8 = 0 + 8
−4x = 8
Step 4: Divide both sides by -4.
−4x/−4
= 8/−4
x = −2